Effect of laparoscopic insemination on reproductive performance of indigenous Cine Capari sheep - KARACA, ORHAN; CEMAL, IBRAHIM; YILMAZ, ONUR; YILMAZ, MURAT (The Indian Journal of Animal Sciences, 2012)
The feasibility of use of laparoscopic artificial insemination (LAI) method was investigated in endangered indigenous Cine Capari sheep breed under conservation. Setting the mating plans and controlling the inbreeding may be possible with the use of effective artificial insemination techniques. In the present study, 23 and 46 ewes showing estrus at 2002–2003 and 2008–2009 mating seasons were laparoscopically inseminated with diluted fresh semen from 6 and 9 rams, respectively. Data were evaluated with respect to gestation length, litter size, duration between sponge removal and beginning of estrus activity (DBSR-BOA), duration between beginning of estrus activity and LAI (DBSR-LAI) and AI success rate. The least square means for mentioned traits were found as 150.3 days, 1.36, 39.98 h, 22.31 h and 69.57% for 2003–2004 lambing season and 148.70 days, 1.41, 41.18 h, 18.35 h and 63.04% for 2008–2009 lambing season, respectively. The difference between means of years were not statistically significant for all the evaluated variables except gestation length. Our results showed that LAI will be a useful tool in activities to conserve Cine Capari sheep as a genetic resource.